Legal Protection for Criminal Justice: A Book Review ‘Restorative Justice di Indonesia’, Ahmad Syharil Yunus SH and Dr Irsyad Dahri SH MH, Guepedia, Bogor Indonesia, 2021, 142 pages, ISBN 978-623-5525-98-3 (Universitas Negeri Semarang, 2022)
The book entitled “Restorative Justice di Indonesia” was written by Ahmad Syahril Yunus, S.H. and Dr. Irsyad Dahri, S.H., M.H. Restorative Justice is the restoration, compensation, and repayment of a part of the relationship between the victims and perpetrators, as well as the society regarding the prosperity or conciliation in criminal justice system. Specifically, this book focuses on the steps involved in implementing Restorative Justice and social justice responses for criminal victims in Indonesia. This book also presents empirical data that shows how Restorative Justice has been used in legal practice by several countries, how victims and perpetrators respond to a new perspective on the legal system through the resolution of Restorative Justice, and how far this can be used effectively to create a standard of punishment and compensation based on fair and balanced treatment of victims and perpetrators.